Bombacaceae endémicas del Perú - León, Blanca (2006)
The Bombacaceae are recognized here as distinct from the Malvaceae, with which it forms a natural group (see Judd et al. 1997, and web site of the Angiosperm Phylogeny Group). In Peru, the Bombacaceae include 15 genera and 56 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), mostly trees. Seven endemic species in five genera are recognized here. Endemic species are found mainly in Dry Forests and Humid Lowland Amazonian Forests regions, between 1300 and 3000 m elevation. We applied IUCN categories and criteria to four of them. None of the species have been recorded to date within Peru’s protected areas system.